Assessment of Physico-Chemical Parameters of Soil of Muthannan Kulam Wetland, Coimbatore, Tamil Nadu, India - Manimegalai, K; Sukanya, S (International Journal of Applied Sciences and Biotechnology, 2014)
Soil serves as a more reliable index for productivity than water qualities. The productivity of any pond depends largely on the quality of bottom soil that is “store house of nutrients.” The present paper deals with the study of physicochemical parameters like organic carbon, pH, Electrical conductivity, Nitrogen, Phosphorus, Potassium of soil from Muthannan Kulam,Coimbatore (March 2013- May 2013). Analysis for the above parameters indicated contamination of the soil quality due to some anthropogenic activities. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10769 Int J Appl Sci Biotechnol, Vol. 2(3): 302-304